The Influence of an Enriched Sport Program on Children’s Sport Motivation in the School Context: The ESA PROGRAM - Gentile, Ambra; Boca, Stefano; Demetriou, Yolanda; Sturm, David; Pajaujiene, Simona; Zuoziene, Ilona Judita; Sahin, Fatma Nese; Güler, Özkan; Gómez-López, Manuel; Borrego, Carla Chicau; Matosic, Doris; Bianco, Antonino; et al. (Frontiers in Psychology, 2020)
Purpose. Sport is a great tool for enhancing physical and psychological well-being. Physical activity, besides the evident positive effect on body development, has proven to boost executive functions, especially if the sport program is enriched with cognitive stimuli. The challenge created by an enriched sport program could also enhance children’s motivation during physical education classes and push them to love sport in general. Therefore, the purpose of this paper is to test if a sport program enriched by cognitive stimuli may improve kids’ motivation or take them out from a state of amotivation. Methods. A sample of 342 school children (203 boys, 139 girls) took part in the study. Participants were asked to complete a battery of motivation and perceived social support questionnaires before and after they completed the ESA Program, a sport program enriched with cognitive stimuli. Moreover, parents of these children attended four seminars about the importance of supporting children for the practice of regular physical activity (PA). A control group consisting of children that attended the ordinary physical education school class was also included. Results. A repeated measures MANOVA model showed that the ESA Program was able to improve children’s general motivation, in particular the intrinsic motivation. The program was not effective in social support, but, independently from the group, the family social support in sports activities decreased for females. Conclusion. Apart from cognitive improvement, the ESA Program can have beneficial effects on children's sports motivation in physical education, but not on perceived social support.